The interplay of service quality, satisfaction, and trust: A systematic review and framework for B2B customer loyalty - Andita, Andita; Wibawa, Berto Mulia (Edelweiss Applied Science and Technology, 2026)
This systematic literature review examines the impact of service quality, customer satisfaction, and customer loyalty in the Business-to-Business (B2B) sector, considering the roles of product quality, price, and trust within a unified analytical framework. Utilizing the PRISMA 2020 protocol, the review consolidated results from 26 peer-reviewed empirical studies published between 2019 and 2024, sourced from the Scopus database. The review reveals that service quality dimensions, particularly reliability, responsiveness, timely delivery, and trust in suppliers, have a significant influence on customer satisfaction, which in turn drives customer loyalty. Customer satisfaction mediates the relationship between service quality, product quality, pricing strategies, and customer loyalty outcomes. Moreover, trust was identified as a critical moderating factor that strengthens these relationships, especially in long-term B2B interactions. The study highlights the challenges businesses face in managing diversified customer relationships, integrating digital and traditional service channels, and optimizing pricing strategies. Conversely, key opportunities for leveraging digital technologies, such as AI, to develop personalized service offerings and enhance customer-oriented capabilities were identified. This study contributes to the literature by offering a comprehensive framework that integrates service quality, satisfaction, trust, and loyalty, and provides actionable insights for B2B managers to enhance customer relationships, foster loyalty, and sustain competitive advantage in an evolving marketplace.